Peran Komunikasi Dalam Kesadaran Publik Mengenai Kesehatan Mental Seseorang - Nelis Novita Sari; Nina Yuliana (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Mental health is a global concern, especally as rates of depression, anxiety and suicide increase. With depression a leading cause of disability worldwide and anxiety a serious health problem, according to the world health organization (WHO), unerstanding the role of communication in mental health has become increasingly important. This research aims to understand the role of communication regarding someone experience mental health problems by determining effective communication strategies. The methof used is by going into the field to analyze interview and observation data. Based on the results of field analysis, environmental factors are the main cause of someone experiencing mental health problems. And, the factors could be those closest to us, namely our own family, friends and companions. As the results of interview data and observations have been made, it is very important to pay more attention to a person's mental health. Especially, yourself. To manage stress well we can do things that can attract positive energy to ourselves, this is what people usually do when they are stressed but don't want to get lost in their own thoughts. to the public and society to care more about people around us who have mental health problems, this can reduce the increasing number of depression rates throughout the world and prevent the death rate of people who try to commit suicide.